2020
DOI: 10.1007/s00442-020-04642-8
|View full text |Cite
|
Sign up to set email alerts
|

Parental effects influence life history traits and covary with an environmental cline in common frog populations

Abstract: Across latitudinal clines, the juvenile developmental rates of ectotherms often covary with the length of the growing season, due to life-history trade-offs imposed by the time-constrained environments. However, as the start of the growing season often varies substantially across years, adaptive parental effects on juvenile developmental rates may mediate the costs of a delayed season. By employing a meta-analysis, we tested whether larval developmental rates across a latitudinal cline of the common frog (Rana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…In our study, individuals that experienced a hatching delay after the exposure to cold temperature that arrested embryonic development, accelerated larval development, metamorphosed in a shorter time, and recovered most of the developmental delay, even after a 12‐day hatching delay. These results agree with theoretical models that predict faster life histories in organisms facing time‐constrained environments (Rowe and Ludwig 1991, Werner and Anholt 1993, Abrams et al 1996), and confirm a common pattern observed in many ectotherms living in seasonal environments (Johansson and Rowe 1999, De Block and Stoks 2004, 2005, Gotthard 2008, Śniegula et al 2012, Rowiński et al 2020), including amphibians (Orizaola et al 2010, 2016Richter‐Boix et al 2014). Developmental acceleration in response to phenological change took place with little change in mass at metamorphosis within each temperature–food treatment, which likely reflects the ecological relevance that body mass has for fitness during the adulthood in ectotherms, and specifically in species with complex life cycles (Rowe and Ludwig 1991, Altwegg and Reyer 2003, Earl and Whiteman 2015).…”
Section: Discussionsupporting
confidence: 88%
“…In our study, individuals that experienced a hatching delay after the exposure to cold temperature that arrested embryonic development, accelerated larval development, metamorphosed in a shorter time, and recovered most of the developmental delay, even after a 12‐day hatching delay. These results agree with theoretical models that predict faster life histories in organisms facing time‐constrained environments (Rowe and Ludwig 1991, Werner and Anholt 1993, Abrams et al 1996), and confirm a common pattern observed in many ectotherms living in seasonal environments (Johansson and Rowe 1999, De Block and Stoks 2004, 2005, Gotthard 2008, Śniegula et al 2012, Rowiński et al 2020), including amphibians (Orizaola et al 2010, 2016Richter‐Boix et al 2014). Developmental acceleration in response to phenological change took place with little change in mass at metamorphosis within each temperature–food treatment, which likely reflects the ecological relevance that body mass has for fitness during the adulthood in ectotherms, and specifically in species with complex life cycles (Rowe and Ludwig 1991, Altwegg and Reyer 2003, Earl and Whiteman 2015).…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, maternal effects may also be neutral or even negative for offspring fitness in some populations (Marshall & Uller, 2007; Mousseau & Fox, 1998; Telemeco et al., 2017). Nonetheless, despite the importance of maternal effects in the flexible and rapid responses of ectothermic vertebrates to environmental change (Galloway & Etterson, 2007; Ma et al., 2014; Rando & Verstrepen, 2007; Rowinski et al., 2020; Shama et al., 2014), how maternal effects shape offspring life‐history traits remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, UVR impacts on DNA damage, methylation, chromatin remodelling and gene expression patterns that may have epigenetic consequences affecting survivability of the next generation (De Oliveira et al, 2020;Ho & Burggren, 2010;Rowinski et al, 2020). For example, Ding et al (2019) observed UVRinduced trans-generational effects on hatching success and larval size in sea urchins (Strongylocentrotus intermediusa).…”
Section: Uvr-induced Carryover Effects In Amphibians: Future Directionsmentioning
confidence: 99%